Effect of Benzyl Adenine Concentration on Callus Induction of Geranium Plants (Pelargonium graveolens L'Her) from Petiole and Leaf Explants - Moch Faizul Huda; Serafinah Indriyani; Wahyu Widoretno (Journal of Experimental Life Science)
Geranium plant (Pelargonium graveolens L'Her) is one of the geranium oil producing plants that has many benefits. Callus culture is a technique that can be used to plant multiplication and increase production of secondary metabolites. This study aims to determine the effect of the concentration of Benzyl Adenine on the formation of geranium callus from petiole and leaf explants. Callus induction was carried out by culturing petiole and leaf explants on MS medium + 0.1 mg.L-1 NAA + Benzyl Adenine (0; 0.5; 1; 1.5 and 2 mg.L-1). Callus morphological parameters, percentage of callus formation, and time of first callus formation were observed. The formation of geranium callus influenced by the explant type and the concentration of Benzyl Adenine. In the 2nd week, the geranium callus was initiated, light green colored with a compact callus texture. At 4th week, the percentage of callus formation containing NAA 0.1 mg.L-1 of petiole and leaf explants was 20% and 8%, whereas the percentage of callus formation on medium containing 0.1 mg.L-1 NAA combined with 0.5-2 mg.L-1 Benzyl Adenine of petiole and leaf explants was 52-80% and 24-52%. The best percentage of callus formation was found on the culture medium containing 1 mg.L-1 Benzyl Adenine, equaled 80% of petiole explants, and 52% of leaf explants.